CPK28-mediated Ca2+ signaling regulates STOP1 localization and accumulation to facilitate plant aluminum resistance - Yingtang Ma; Hailiang Zheng; Ina Schmitz-Thom; Jiawen Wang; Fanglin Zhou; Chongyang Li; Yaling Zhang; Yiqiu Cheng; Daisuke Miki; Jörg Kudla; Chao-Feng Huang (Nature Communications)
Abstract The transcription factor SENSITIVE TO PROTON RHIZOTOXICITY 1 (STOP1) functions as a crucial integrator of plant responses to various stresses, including aluminum (Al) stress. Its stability and accumulation are modulated by stress-specific post-translational mechanisms such as phosphorylation and ubiquitination. However, the upstream signaling mechanisms governing these modifications remain poorly understood. Here, we reveal that Ca2+ signaling and Ca2+-dependent phosphorylation are essential for Al stress-responsive regulation of STOP1. Al exposure specifically induces rapid, spatio-temporally defined biphasic Ca2+ signals in Arabidopsis roots and concomitantly activates the Ca2+-dependent kinase CPK28. Al-activated CPK28 phosphorylates STOP1 at Ser163, a modification that promotes the nuclear localization of STOP1 and prevents its degradation by inhibiting its interaction with the F-box protein RAE1. This phosphorylation enhances STOP1 accumulation and Al resistance. Our findings identify Ser163 phosphorylation as a key molecular switch and establish a Ca2+-CPK28-STOP1 signaling axis critical for plant adaptation to Al stress.